Between wisdom and Torah discourses on wisdom and law in Second Temple Judaism - Kwon, JiSeong James 1977-; Bledsoe, Seth A.; Walter de Gruyter GmbH & Co. KG (Berlin/Boston Walter De Gruyter GmbH, 2023)
Intro -- Acknowledgement -- Contents -- Preface -- Abbreviations -- Part I: Wisdom &amp -- amp -- Torah in Instructional Literature -- Instructions and Torah in Proverbs 1-9: Assessing the Confluence of Torah and Wisdom in Proverbs -- Proverbs 28 and the Discourse on Wisdom and Torah in the Book of Proverbs -- Ben Sira and His Grandson on Torah and Wisdom: Similar or Divergent Views? -- Part II: Wisdom &amp -- amp -- Torah in Skeptical-Critical Discourse -- "Things Too Wondrous" (Job 42:3): The Torah and the Limits of Knowledge in the Book of Job -- Failing to be Wise: The Case of Qohelet -- Wisdom and Law in the Book of Wisdom: A New Type of Relationship -- Sofia and Nomos in the Wisdom of Solomon -- Part III: Wisdom &amp -- amp -- Torah in Legal Discourse -- Explaining the "Confluence" of Biblical Wisdom and Torah: An Anthropological and Rhetorical Approach -- The Amalgamation of "Wisdom" in the Post-Deuteronomistic Deuteronomy of the Persian and Hellenistic Periods -- Law and Wisdom in the Epitaph of Abramos, Communal Magistrate (JIGRE 39 = SB 5765) -- Part IV: Wisdom &amp -- amp -- Torah in Poetic Reflection -- The Song of Songs: Torah, Creation, Celebration, and Libertinism -- Wisdom and Torah in the Hodayot and the Great Psalms Scroll: The Place of Prayer in Understanding Some Early Jewish Pedagogy -- Part V: Wisdom &amp -- amp -- Torah in Narrative Imagination -- The Question of Wisdom Influence in the Composition of the Joseph Narrative -- Ahiqar the "Patriarch": Tobit's Interpretation of the Wisdom of Ahiqar through a Torahizing Lens -- Index of Modern Authors -- Index of Sources.
Description based on publisher supplied metadata and other sources
Keywords: Bible - Critique, interprétation, etc. juives; Bible; 586 B.C.-210 A.D; Sagesse - Aspect religieux - Judaïsme; Littérature sapientiale - Critique, interprétation, etc; Judaïsme - Histoire - 586 av. J.-C.-210 (Période postexilique); Judaism - Post-exilic period (Judaism); Wisdom Literature; Wisdom - Religious aspects - Judaism; Criticism, interpretation, etc; History; Aufsatzsammlung